Primary Desmoplastic Small Round Cell Tumor of the Femur: Case Report and Review of a Rare Intraosseous Malignancy. (May 2022) - Sharma, Aarti E.; deVries, John A.; Agrawal, Caitlin; Haydon, Rex C.; Krausz, Thomas; Pytel, Peter; Cipriani, Nicole A.
Background: Desmoplastic small round cell tumors (DSRCT) are malignant neoplasms of young males arising most commonly in the abdominopelvic cavity, with a subset originating from extra-abdominal soft tissues. As either primary or metastatic lesions, they are rare in intraosseous sites.Case Presentation: We describe the fifth report of primary DSRCT of bone. A healthy 18-year old male presented with a blastic, 17 cm lesion within the left distal femur, suspicious for osteosarcoma or Ewing sarcoma. Subsequent biopsy revealed nests of small round blue cells infiltrating through a desmoplastic stroma. These cells were diffusely positive for epithelial markers, with paranuclear staining for desmin and focal reactivity with NSE. Break-apart FISH revealed a rearrangement in EWSR1, and RNA fusion panel confirmed WT1 as its partner in the pathognomonic t(11;22)(p13;q12) rearrangement. PET/CT showed widespread metastatic disease to visceral and bony sites.Conclusions : Due to their rarity as well as clinicopathologic and immunomorphologic overlap, primary intraosseous DSRCT can create diagnostic challenges with the more frequently encountered tumors of bone.